A novel highly fluorescent S, N, O co-doped carbon dots for biosensing and bioimaging of copper ions in live cells. Issue 73 (18th December 2018) - Dai, Yanyu; Liu, Zhichao; Bai, Yunfeng; Chen, Zezhong; Qin, Jun; Feng, Feng
Abstract : In this study, novel highly fluorescent sulfur, nitrogen, and oxygen co-doped carbon dots (S, N, O-CDs) were prepared from m -phenylenediamine and sulfamide by using the hydrothermal method. Abstract : In this study, novel highly fluorescent sulfur, nitrogen, and oxygen co-doped carbon dots (S, N, O-CDs) were prepared from m -phenylenediamine and sulfamide by using the hydrothermal method. The prepared S, N, O-CDs show high doping rate and fluorescence yield as well as long-term fluorescence stability. In addition, S, N, O-CDs show good fluorescence response towards Cu 2+ over a concentration range of 2–60 μM with a detection limit of 0.29 μM. Taking advantages of the properties of S, N, O-CDs including high selectivity and low cytotoxicity, S, N, O-CDs were successfully applied for Cu 2+ sensing and imaging in the cells and O2 ˙ − -induced Cu 2+ increase in the cells was observed. Furthermore, on account of strong complexation between Cu 2+ and pyrophosphate ion (PPi) as well as specific hydrolysis ability of alkaline phosphatase (ALP) towards PPi, PPi and ALP were further detected with high selectivity based on S, N, O-CDs/Cu 2+ system. The prepared S, N, O-CDs showed good detection results for PPi and ALP with detection limits of 0.44 μM and 1.03 U L −1, respectively. Moreover, the developed method also realized PPi and ALP detection in real samples.